Volvariella Volvacea Mushroom Production in Some Growing Media - Noertjahyani, Noertjahyani; Hanafi, Harri; Komariah, Ai; Amalia, Lia; Ulfah, Indriana; Budiasih, R. (Jurnal Agrosci, 2025)
Background. Volvariella volvacea (straw mushroom) is a high-demand agricultural commodity. Rice straw is used as a planting medium in this crop production. During the harvest season, this type of media is abundant. Other press must be used to produce straw mushrooms continuously. Aims. This research aims to study the growth and yield of the mushroom V. volvacea on various growing media. Karawang regency hosted an experimental study. Methods. The experimental design was a randomized complete block design with six treatments and four replications. The treatment of mushroom growing media in rice straw, rice husk, waste from textile fabric (cotton), and three other treatments was a 1:1 (v/v) mixture of these planting media. Result. The findings revealed that different planting media had an impact on the growth and yield of straw mushrooms. Conclusion. The highest mushroom production was obtained by combining the growing media ,straw and husk ,in a 1:1 ratio. Implementation. Rice husk can be used as a substitute for straw as a growing medium.